2001
DOI: 10.1038/85294
|View full text |Cite|
|
Sign up to set email alerts
|

Inactivation of Notch1 in immature thymocytes does not perturb CD4 or CD8 T cell development

Abstract: Notch proteins influence cell-fate decisions in many developing systems. Several gain-of-function studies have suggested a critical role for Notch 1 signaling in CD4-CD8 lineage commitment, maturation and survival in the thymus. However, we show here that tissue-specific inactivation of the gene encoding Notch 1 in immature (CD25+CD44-)T cell precursors does not affect subsequent thymocyte development. Neither steady-state numbers nor the rate of production of CD4+ and CD8+ mature thymocytes is perturbed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
249
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(264 citation statements)
references
References 29 publications
13
249
2
Order By: Relevance
“…Models using inducible Notch 1 gene deletion suggested that Notch plays a role at least throughout the DN stages [26]. However, deletion of Notch 1 at the late DN stage does not impair normal thymocyte development [27]. Human thymocyte CD34 1 TN population studied here is a mixture of different thymocyte precursors but contained a large majority of CD1a 1 CD5 1 CD4 À cells (data not shown) corresponding to the DN3 stage in mice.…”
Section: Discussionmentioning
confidence: 72%
“…Models using inducible Notch 1 gene deletion suggested that Notch plays a role at least throughout the DN stages [26]. However, deletion of Notch 1 at the late DN stage does not impair normal thymocyte development [27]. Human thymocyte CD34 1 TN population studied here is a mixture of different thymocyte precursors but contained a large majority of CD1a 1 CD5 1 CD4 À cells (data not shown) corresponding to the DN3 stage in mice.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, our evidence indicates that Notch signaling is ongoing throughout the CD4 Ϫ 8 Ϫ stage, and we have shown that such signaling, at least within unseparated E15 CD4 Ϫ 8 Ϫ thymocytes, is dependent upon interaction with thymic epithelial cells. As the currently available inducible Notch knockout animals result in deletion either before or toward the end of the DN stage (8,29,30), the physiological relevance of this activity remains to be determined. Likewise, the roles of individual Notch ligands expressed by thymic epithelium in regulating intrathymic Notch activity for T/B lineage choice and for other lineage choices (e.g., ␣␤/␥␦ vs NK) within the T pathway are important issues still to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Although two distinct strains of conditional Notch1-KO mice share no defects in the generation of mature SP thymocytes (18,19), overexpression experiments have suggested that constitutively active Notch1 biases thymocyte development toward the CD8 lineage or even prevents the maturation of SP cells completely (20 -23). In the light of this ongoing debate, we have generated transgenic rats expressing Notch1IC in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that these differences partly derive from the individual experimental approaches taken. Two strains of conditional Notch1-knockout (KO) mice where the gene had been deleted at different time points during the DN stage of thymocyte development failed to reveal any effect on the generation of SP thymocytes (18,19). Thus, Notch1 does not play an essential, nonredundant role in this lineage decision.…”
mentioning
confidence: 99%